A Comprehensive Synthesis and Characterization via the Chemical Sol-Gel Method - salim abed, firas; Abbas, Lamia K. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2025)
This research presents a synthesis approach for BSCCO superconductor with barium (Ba) substitution, involving a minor substitution at a fixed ratio of lead (Pb) and europium (Eu) through the chemical sol-gel method. The systematic exploration involves incorporating 0.1 of Eu instead of Bi into the BSCCO matrix to comprehend its impact on superconducting properties and the feasibility of producing superconducting material using the sol-gel route. Superconductor samples denoted as Bi1.6Pb0.3Eu0.1Sr2-yBayCa2Cu3O10+δ, where y varies from 0.0 to 0.3, were prepared. The investigation focused on understanding the effect of partially substituting Ba for Sr on superconducting properties. Transmitted electron microscopy (TEM) results revealed the creation of nanoparticles with an average diameter of 104.7 nm using the sol-gel technique. X-ray diffraction (XRD) analysis exhibited mainly the high-Tc phase (2223) compared to the low phase (2212) and a higher a/c ratio was observed at y=0.1. Electrical resistivity measurements demonstrated an improvement in critical temperature (Tc), reaching 113 K, and an increase in oxygen content at the same ratio. This comprehensive investigation explores the influence of Ba substitution on the structural and superconducting properties of the BSCCO system prepared by the sol-gel technique for further exploration and optimization of these HTS for specific applications.